Sistema de exportaciones de las unidades económicas artesanales de San Antonio de Ibarra que elaboran artesanías en madera: caso de la unidad artesanal económica del Sr. Alonso López - Granja Proaño, Luis Ricardo (2019)
In Ecuador the art of carving wood is one of the oldest traditions that have been passed down from generation way, initially wooden handicrafts are strictly used for practical purposes, but later appeared his decorative applications and utilities becoming an important source of income and employment. It is for this reason that the Ecuadorian handicraft products must be prepared to be able to compete in various markets around the world, knowing that these markets can have big advantages: quality products, high technology, low costs and work done by hand skilled labor. However Ecuador, despite being a less developed country has excellent handicrafts. The crafts sector has economic and social importance for our country: preserve the culture and traditions contribute to the growth of the economy, generating foreign exchange earnings, generating direct and indirect employment, further their development potential is very large and it has high quality handicrafts. Among the features most valued in the Ecuadorian handicraft products they are: artistic expression, ethnicity, specific geographical origin, prehispanic culture, heritage and colonial tradition. This degree project shows the development of a system of export concerning economic unit craft Mr. Alonso Lopez said artisan crafts made of wood, the same that is located in the rural parish of San Antonio de Ibarra. It began with a descriptive study of 285 affordable units being included the craft in question, to analyze the external and internal aspects of them. The paper argues the research problem, a theoretical framework for the purpose of guiding the conceptual bases, then the methodology used in the research, results and finally the proposal which is focused on the creation of a web page through the acquisition of a for hosting the workshop under study\; well in this paragraph the US market which is the main export destination for crafts from our country is analyzed, besides being the main trading partner of Ecuador in relation to economic and trade policies that have been established around these two nations.